If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(x+6)+3=10(x-4)-2
We move all terms to the left:
9(x+6)+3-(10(x-4)-2)=0
We multiply parentheses
9x-(10(x-4)-2)+54+3=0
We calculate terms in parentheses: -(10(x-4)-2), so:We add all the numbers together, and all the variables
10(x-4)-2
We multiply parentheses
10x-40-2
We add all the numbers together, and all the variables
10x-42
Back to the equation:
-(10x-42)
9x-(10x-42)+57=0
We get rid of parentheses
9x-10x+42+57=0
We add all the numbers together, and all the variables
-1x+99=0
We move all terms containing x to the left, all other terms to the right
-x=-99
x=-99/-1
x=+99
| -5y/9=20 | | 5-x/2=9 | | (3+x)^2=169 | | -7u-1=-9+u | | 3(7+2x)+3=3( | | 9x+x=1+4x | | 50/x=3+2 | | 5f+2=-4+6-8f | | 5z-6=4-3z | | 75+6,25x=90+4.75x | | 10x-3=40x=9 | | 8x-(-4)=20 | | 3.28t+25=-1.72t | | n-1+2/3=-2 | | 3x^2-9+2=26 | | 10/18=n/8 | | 14-x+-4=3(x+9)-10 | | 4(2x-10)=-88 | | 3/4t=22 | | 6(4p-4)=32p | | 19b-25-3b=4b—1 | | 9/54=1)d | | 2*x*x=1 | | 125m-75m+48,000=51,000-200m | | n+11×8n=29 | | 6(28p-4)=32p | | (n•5)•4=(4•5)•2 | | 5a-3+2a=3+3a | | 21u=819 | | 2x-5(x-4)=-2+5x-42 | | 7^(4x-1)=49 | | 3(x+3=12 |